Health Education Concerning Posyandu Elderly To Motivation And Family Attitude To Accompany Elderly - I Made Suwena (Journal of Applied Nursing and Health, 2019)
The increase in life expectancy has led to an increase in the number of elderly people in Indonesia. Welfare services for the elderly in general can be said to be still new. This is because the priority given to the elderly population has only recently begun to be considered. Objective To find out the effect of Health Education on Posyandu Elderly Against Motivation and Family Attitudes to Accompany Elderly to Posbindu, Sinorang Health Center, Batui Selatan Subdistrict, Banggai Regency, Central Sulawesi. The design used in this study is true experiment. The population is all families with the elderly. The sample size was 40 respondents using Simple Random Sampling technique. The independent variable of research is health education. The dependent variable is Motivation and Attitude. Data were collected using a questionnaire, then data were analyzed using the Wilcoxon and Man Whitney tests with a significance level of α ≤ 0.05. The results showed that most of the respondents before the intervention had sufficient motivation as much as 10 respondents (50%), after the intervention had as much motivation as 9 respondents (45%), respondents before the intervention had sufficient attitudes as many as 11 respondents (55%), after the intervention has attitudes of 10 respondents (50%), Wilcoxon statistical test there is an influence of the Posyandu Elderly Health Education Against Motivation to Accompany the Elderly, there is an influence of the Posyandu Elderly Health Education Against the attitude to Accompany the Elderly, Mann-whitney statistical test there are differences in the intervention group with the group Control Against Motivation to Accompany Elderly, there is a difference in the intervention group with the control group Towards Attitude to Accompany Elderly. There is an influence of Health Education on Posyandu Elderly Against Motivation and Attitudes of Families to Accompany Elderly to Posbindu, Sinorang Health Center, South Batui District, Banggai Regency, Central Sulawesi.